2010
DOI: 10.4161/auto.6.2.11042
|View full text |Cite|
|
Sign up to set email alerts
|

Macroautophagy and ERK phosphorylation counteract the anti-proliferative effect of proteasome inhibitor in gastric cancer cells

Abstract: Sung (2010) Macroautophagy and ERK phosphorylation counteract the anti-proliferative effect of proteasome inhibitor in gastric cancer cells, Autophagy, 6:2, 228-238,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…On the contrary, in the thyroid cancer cell line FRO82-1 bortezomib, as well as epoxomicin, increased the expression of LC3-II protein but reduced the protein level of Beclin-1 [78]. Another proteasome inhibitor MG-132, in a time-and dose-dependent manner increased the content of LC3-II in HCT116 cells [75], colon cancer cells HT-29 [79,80] and SW1116 [80], thyroid cancer cells [78], gastric cancer cells [81], HeLa cells [82], prostate cancer DU145 cells and MEFs [75] and in immortalized dopaminergic neuronal N27 cell line [83]. In the majority of the above-mentioned experimental conditions there were no significant changes in Beclin-1 levels, and in thyroid cancer cells a decrease of Beclin-1 protein level has been reported [78].…”
Section: Effects Of Different Classes Of Proteasome Inhibitors On Autmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in the thyroid cancer cell line FRO82-1 bortezomib, as well as epoxomicin, increased the expression of LC3-II protein but reduced the protein level of Beclin-1 [78]. Another proteasome inhibitor MG-132, in a time-and dose-dependent manner increased the content of LC3-II in HCT116 cells [75], colon cancer cells HT-29 [79,80] and SW1116 [80], thyroid cancer cells [78], gastric cancer cells [81], HeLa cells [82], prostate cancer DU145 cells and MEFs [75] and in immortalized dopaminergic neuronal N27 cell line [83]. In the majority of the above-mentioned experimental conditions there were no significant changes in Beclin-1 levels, and in thyroid cancer cells a decrease of Beclin-1 protein level has been reported [78].…”
Section: Effects Of Different Classes Of Proteasome Inhibitors On Autmentioning
confidence: 99%
“…Inhibited mTORC1 disinhibits kinase Ulk1/2 activities, resulting in FIP200 phosphorylation, which is required for the early stages of autophagosome formation [50]. It has been reported that after MG-132 application in various experimental cell culture models [79][80][81]121] characteristic features of increased autophagy were accompanied by pronounced inhibition of mTORC1-mediated phosphorylation of 4E-BP1 and S6K. Initially, the mechanism by which proteasome inhibition resulted in the disruption of mTORC1 remained vague, but recent studies using bortezomib as an autophagy inducer showing up-regulation of sestrin-2 (SESN2/Hi95) [122] have shed new light on this problem.…”
Section: Pi3k/akt/mtormentioning
confidence: 99%
“…15 When proteasomal degradation is either overwhelmed or inhibited, misfolded and ubiquitinated proteins that accumulate in the cytosol are transported to perinuclear aggresomes, which then are sequestered within autophagosomes that subsequently fuse with lysosomes for degradation of their contents. [16][17][18] Simultaneous proteasome and autophagy inhibition therefore leads to accumulation of ubiquitinated proteins and synergistic cytotoxicity in preclinical models. 19,20 Hydroxychloroquine (HCQ), a drug with a favorable and well-defined toxicity profile that is commonly used to treat autoimmune diseases, is a known inhibitor of autophagy.…”
Section: Combined Autophagy and Proteasome Inhibitionmentioning
confidence: 99%
“…Autophagy is induced by different forms of cancer therapy, including conventional chemotherapeutic drugs, novel targeted cancer therapeutics and ionizing radiation, in various types of solid and hematological malignancies (Table 2) (Han et al, 2007(Han et al, , 2008Kim et al, 2007Kim et al, , 2008bKim et al, , 2009aMaiuri et al, 2007b;Kamitsuji et al, 2008;Meschini et al, 2008;Qadir et al, 2008;Turcotte et al, 2008;Fu et al, 2009;Lorin et al, 2009;Tormo et al, 2009;Fan et al, 2010;Gupta et al, 2010;Huang and Sinicrope, 2010;Li and Fan, 2010;Voss et al, 2010;Yacoub et al, 2010;Wu et al, 2010c;Lian et al, 2011;O'Donovan et al, 2011). In some circumstances, autophagy mediates the cytotoxic or cytostatic effect of anticancer agents, in which blockade of autophagy abolishes the therapeutic actions.…”
Section: Autophagy and Its Outcome Determinants In Cancer Therapymentioning
confidence: 99%